Hubungan Tugas Perkembangan Keluarga Tahap II (Childbearing Family) dengan Kelengkapan Imunisasi DPT pada Bayi di Wilayah Kerja Puskesmas Mangli Kabupaten Jember (The Correlation Between Second Stage (Childbearing) of Family Development Task with Complete - Myla Alisa Novita Sari; Latifa Aini Susumaningrum; Lantin Sulistyorini (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The second stage of family development start from childbirthing untill baby 30 monthsold. Immunization is one of health attention in that stage. One kind of immunization isDPT immunization which given completely for baby between 2-11 months old. Thisresearch aimed to analize the correlation between second stage family developmenttask with DPT immunization completeness. This research was observasional analiticusing study cross sectional. Method of collecting samples was proportionate randomsampling and total of samples got are 68 respondents. Data were analyzed withSpearman Correlation. Statistical test showed that significancy was 0,089 withcorrelation coefficient was 0,208, which means there was no significant correlationbetween second stage (childbearing) of family development task with DPTimmunization completeness in Working Area of Mangli Public Health Centre in Jember.The conclussion of this study is the family are exxpected to maintain the completenessDPT immunization of baby, especially in second stage of family development.Keywords: family, childbearing, development task, DPT immunization